2019
DOI: 10.1155/2019/3756092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propolis Preparations on Transepithelial Electrical Potential, Resistance, and Ion Transport in In Vitro Study

Abstract: Background Propolis and its ethanol extract show positive germicidal, bacteriostatic, and anti-inflammatory antioxidants and regenerative properties after use on the surface of the skin. Propolis is in common use in production of cosmetics and in folk medicine. The influence of this resinous mixture on ion channels, channels located in skin cells membranes and skin electrical resistance, was not explained. Objective The main aim of the study was the evaluation of electrophysiological skin parameters during mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Propolis is generally made up of 50% resinous substances, 30% wax, 10% essential oils, 5% pollens, and 5% minor constituents such as impurities, amino acids, soils, and dead bees. e propolis extracts are known to contain numerous beneficial chemical compounds and biological activities that can be utilised in sectors such as pharmaceutical and health for their antimicrobial, antifungal, antiviral, anticancer, antidiabetic, antioxidant activities, and many more [1,2]. It has been observed that honey bees mostly construct their nests or combs using waxes, unlike stingless bees, which often build their nests using plant resins collected or propolis.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis is generally made up of 50% resinous substances, 30% wax, 10% essential oils, 5% pollens, and 5% minor constituents such as impurities, amino acids, soils, and dead bees. e propolis extracts are known to contain numerous beneficial chemical compounds and biological activities that can be utilised in sectors such as pharmaceutical and health for their antimicrobial, antifungal, antiviral, anticancer, antidiabetic, antioxidant activities, and many more [1,2]. It has been observed that honey bees mostly construct their nests or combs using waxes, unlike stingless bees, which often build their nests using plant resins collected or propolis.…”
Section: Introductionmentioning
confidence: 99%